CFD Modeling of Single-Drop Hydrodynamics at Submerged Nozzles: Validation with TBP-Dodecane and Nitric Acid System and Parametric Analysis. Issue 2 (23rd February 2019) - Roy, Amitava; Sen, Nirvik; Singh, K. K.; Shenoy, K. T.; Grover, R. B.
ABSTRACT: Solvent extraction is an important separation process having many applications in chemical process industry, wastewater treatment, and separation of nuclear materials in the front-end and back-end of the closed nuclear fuel cycle. It is essentially based on dispersion of one liquid phase into another immiscible liquid phase in the form of drops. This study, which is relevant to solvent extraction, is focused on computational fluid dynamics simulations of one of the mechanisms to generate dispersion in which drops are generated by flowing a liquid through a nozzle submerged in another immiscible liquid. Two different orientations of nozzles, vertically upward and vertically downward, are considered. Transient simulations are carried out using the phase-field method for tracking the interface between the two immiscible liquids. Validation has been done with the experimental data of 30%TBP-dodecane and nitric acid system. The validated model is used to perform parametric analysis to get insights into the effects of physical properties (interfacial tension, contact angle, and density difference) on drop formation phenomenon. The results from parametric analysis are used to obtain correlations to estimate drop diameter at upward-oriented and downward-oriented nozzles.